Assaracus : a journal of gay poetry. (Little Rock : Sibling Rivalry Press, 2011)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : PO Box 26147, Little Rock AR 72221
Engels
Periodiek